Antioxidant and antimicrobial attributes and phenolics of different solvent extracts from leaves, flowers and bark of Gold Mohar [Delonix regia (Bojer ex Hook.) Raf.] - Shabir, Ghulam; Anwar, Farooq; Sultana, Bushra; Khalid, Zafar M.; Afzal, Muhammad; Khan, Qaiser M.; Ashrafuzzaman, Muhammad (MDPI, 2011)
This paper describes the antioxidant and antimicrobial activities and phenolic components of different solvent (absolute methanol, absolute ethanol, absolute acetone, 80% methanol, 80% ethanol, 80% acetone and deionized water) extracts of leaves, flowers and bark of Gold Mohar [Delonix regia (Bojer ex Hook.) Raf.]. The extract yields from leaves, flowers and bark ranged from 10.19 to 36.24, 12.97 to 48.47 and 4.22 to 8.48 g/100 g dry weight (DW), respectively. Overall, 80% methanol extract produced from the leaves exhibited significantly (P < 0.05) higher antioxidant activity, with high phenolic contents (3.63 g GAE/100 g DW), total flavonoid contents (1.19 g CE/100 g DW), inhibition of peroxidation (85.54%), DPPH scavenging capacity (IC50 value 8.89 μg/mL) and reducing power (1.87). Similarly, this 80% methanol leaves extract also showed superior antimicrobial activity. HPLC analysis of the 80% methanol extracts for individual phenolics revealed the presence of gallic, protocatechuic and salicylic acid in leaves; gallic, protocatechuic, salicylic, trans-cinnamic and chlorogenic acid in flowers, and gallic acid in bark as the main (amount > 1.50 mg/100 g DW) phenolic acids. Besides, small amounts ( < 1.50 mg/100 g DW) of some other phenolic acids such as sorbic, sinapic, p-coumaric, m-coumaric, ferulic, caffeic, 3-hydroxybenzoic, 4-hydroxycinnamic and 4-hydroxybenzoic acids were also detected. The extracts of the tested parts of Gold Mohar, especially, the leaves, might be valuable for functional food and therapeutic applications.